Phytochemistry and Pharmacology of Oxystelma Esculentum - Chishti, Abdul Wadood; Akram, Muhammad; Rehman, Urooj; Khan, Fahad Said; Iftikhar, Momina; Umaru, Isaac John (African Journal of Biochemistry and Molecular Biology Research, 2025)
Several phytochemicals, including glycosides, alkaloids, flavonoids, and saponins, are present in the widespread medicinal herb Oxystelmaesculentum. These physiologically active substances contribute to the herb's pharmacological properties, which include anti-inflammatory, antioxidant, antibacterial, and antidiabetic effects. Research studies have shown that O. esculentum can be used medicinally to treat a variety of ailments, such as fever, pain, respiratory issues, and digestive issues. It may also have neuroprotective properties and help in blood sugar regulation. Even though its therapeutic qualities appear promising, more research must be done to verify its efficacy, safety, and potential for drug development.